Silver Single Atom in Carbon Nitride Catalyst for Highly Efficient Photocatalytic Hydrogen Evolution - Jiang, Xun‐Heng; Zhang, Long‐Shuai; Liu, Hai‐Yan; Wu, Dai‐She; Wu, Fei‐Yao; Tian, Lei; Liu, Ling‐Ling; Zou, Jian‐Ping; Luo, Sheng‐Lian; Chen, Bing‐Bing (Angewandte Chemie International Edition, 2020)
Single atom catalysts (SACs) with the maximized metal atom efficiency have sparked great attention. However, it is challenging to obtain SACs with high metal loading, high catalytic activity, and good stability. Herein, we demonstrate a new strategy to develop a highly active and stable Ag single atom in carbon nitride (Ag‐N2C2/CN) catalyst with a unique coordination. The Ag atomic dispersion and Ag‐N2C2 configuration have been identified by aberration‐correction high‐angle‐annular‐dark‐field scanning transmission electron microscopy (AC‐HAADF‐STEM) and extended X‐ray absorption. Experiments and DFT calculations further verify that Ag‐N2C2 can reduce the H2 evolution barrier, expand the light absorption range, and improve the charge transfer of CN. As a result, the Ag‐N2C2/CN catalyst exhibits much better H2 evolution activity than the N‐coordinated Ag single atom in CN (Ag‐N4/CN), and is even superior to the Pt nanoparticle‐loaded CN (PtNP/CN). This work provides a new idea for the design and synthesis of SACs with novel configurations and excellent catalytic activity and durability. A new Ag single atom in carbon nitride (Ag‐N2C2/CN) photocatalyst with Ag‐N2C2 configuration is developed. It affords fast charge transfer, high Ag loading, and good stability. Noteworthily, the Ag‐N2C2/CN exhibits much better hydrogen evolution activity than Ag‐N4/CN, and even superior to the platinum‐loaded CN.